Factors influencing healthcare workers' perceptions towards comprehensive emergency obstetric and newborn care - Yusrawati, Yusrawati; Respati, Titik; Sekarwana, Nanan (International Journal of Public Health Science (IJPHS), 2023)
In tertiary hospitals, comprehensive emergency obstetric and newborn care (CEmONC) provides subspecialty care for high-risk maternal and neonatal emergency cases. Healthcare workers (HCWs) play critical roles in hospital services, and their perception affects the quality of care they provide. Hence, this study was conducted to analyze the factors influencing HCWs’ perception regarding CEmONC in a tertiary referral hospital. This cross- sectional study used an electronic questionnaire distributed to 198 CEmONC team members. The sample was selected by convenience sampling, and those who had worked for at least one year were included. The collected data were then analyzed using bivariate and multivariate analysis. Among 119 HCWs, 52.9% had a positive perception towards CEmONC implementation at the hospital. The result of logistic regression analysis found that the significant factors contributing to HCWs’ positive perceptions were good knowledge (AOR=33.484; p=0.001), good attitude (AOR=55.834; p=0.009), high motivation (AOR=12.579; p=0.005), high expectations (AOR =27.106; p=0.002), and good actual performance (AOR=45.879; p=0.003). Age, gender, professional background, and the length of work experience werenot associated with HCWs’ perceptions (p>0.05). Therefore, hospital administrators must regularly evaluate these factors to improve the quality of CEmONC services in the hospital so that maternal and infant mortality rates can be reduced.